Tocilizumab Treatment Affects Intensive Care Unit Admission Rates of COVID-19 Patients in a Dose-dependent Manner - Önal, Burak; Orman, Müjgan; Arslan Ulukan, Zeliha; Çeliker, Esin Oğul; Uzun, Cengiz; Ünal Özcivelek, İrem and Çit, Murtaza and Askar, Safwat Abbas Ali and Azermir, Mansur and Temizel, Mustafa and et al. (Cerrahpaşa Medical Journal, 2021)
Objective: COVID-19 led to a pandemic that continues to spread worldwide. Despite several studies, it is hard to perform a comprehensive study including a high number of patients. Critically ill patients need intensive care units (ICU) and with the increased cost of hospitalization in ICUs, the newly discovered drugs to treat COVID-19 must be cost-effective. We aimed to present the effect of Tocilizumab (TCZ) treatment at different doses on both mortality and days spent in ICU. Methods: We conducted a retrospective study in the Medicana International Istanbul Hospital. We compared the outcome of patients treated with TCZ with the status of mortality and ICU admissions. Results: There was a dramatic decrease in the duration of ICU stay for patients treated with a single 8 mg/kg TCZ dose (P = .006). In addition, the mortality rate decreased with 3 different doses (in a single 4 mg/kg dose, a single 8 mg/kg dose, and a divided 4 mg/kg dose), but increased in a divided 8 mg/kg dose (P = .010). Conclusion: Despite the retrospective design of the study and the small sample size, our findings principally suggest that TCZ might reduce the rate of mortality and the need for ICU admissions in COVID-19 patients. Cite this article as: Önal B, Orman M, Arslan Ulukan Z, et al. Tocilizumab treatment affects intensive care unit admission rates of COVID-19 patients in a dose-dependent manner. Cerrahpaşa Med J. 2021;45(3):177-184.